Incidental midgut malrotation detected during second laparotomy: Case report and literature review. (2015) - Vural, Veli; Türkoğlu, Mehmet Akif; Karatas, Gulnur
Abstract: Introduction: Intestinal malrotation is defined as intestinal nonrotation or incomplete rotation around superior mesenteric artery (SMA), involving anomalies of intestinal fixation as well. The patients may be recognized incidentally during other surgical procedures or at autopsy. Here in, we present a case of midgut malrotation which was diagnosed incidentally during hepaticojejunostomy procedure for benign biliary stricture. Presentation of case: A 46 years old male patient was referred to our clinic with failed surgery for biliary stricture due to extensive adhesions. Prior to our surgery, intestinal malrotation was not reported and noticed by the diagnostic tools. When the patient underwent relaparotomy, midgut malrotation was observed. Discussion: Distruption in the normal embryological development of bowel is the cause of intestinal malrotation. Various anatomic configurations and anomalies resulting from rotation anomalies of midgut. Adult patients are usually asymptomatic and the anomaly is discovered only at autopsy or incidentally at surgery. The role of additional surgery especially in patients with asymptomatic disease related to malrotation is debated. Conclusion: Performing loop hepaticojejunostomy with Braun enteroenterostomy is feasible and acceptable option rather than Roux-N-Y hepaticojejunostomy in case of intestinal malrotation.